2021
DOI: 10.1002/eap.2290
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon is not just for soil scientists: measurement recommendations for diverse practitioners

Abstract: Soil organic carbon (SOC) regulates terrestrial ecosystem functioning, provides diverse energy sources for soil microorganisms, governs soil structure, and regulates the availability of organically bound nutrients. Investigators in increasingly diverse disciplines recognize how quantifying SOC attributes can provide insight about ecological states and processes. Today, multiple research networks collect and provide SOC data, and robust, new technologies are available for managing, sharing, and analyzing large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 221 publications
(264 reference statements)
0
11
0
Order By: Relevance
“…Data providers will often ask "what should I measure?" to be relevant to data aggregation efforts, and there are efforts to provide such guidance (Billings et al, 2021). We have chosen instead to focus on critical spatiotemporal information to allow data to be expanded, contextualized, and annotated.…”
Section: What To Measure and Report?mentioning
confidence: 99%
“…Data providers will often ask "what should I measure?" to be relevant to data aggregation efforts, and there are efforts to provide such guidance (Billings et al, 2021). We have chosen instead to focus on critical spatiotemporal information to allow data to be expanded, contextualized, and annotated.…”
Section: What To Measure and Report?mentioning
confidence: 99%
“…Soils are inherently rooted in time and space, making high resolution spatial and temporal information (including sampling date, latitude, longitude, and geographic datum, and depth of sample) critical for building context and data reuse. Data providers will often ask 'what should I measure' to be relevant to data aggregation efforts, and there are efforts to provide such guidance (Billings et al, 2021). We have chosen instead to focus on critical temporal-location information to allow data to be expanded, contextualized, and annotated.…”
Section: What To Measure and Report?mentioning
confidence: 99%
“…We see a ripe opportunity for harmonizing microbial and biogeochemical SOM models within and across all scales through substrate (plant and microbial) chemistries, which determine SOM composition (from a biogeochemical perspective) as well as the rate and pathway of microbial metabolism (from a microbial perspective). Billings et al (2021) have identified SOM chemistry as a measurement for the next generation of soil C research, highlighting the increasing usage of molecular advances such as Fourier-Transformed Infrared Spectroscopy (FTIR, Cheng et al 2006;Keiluweit et al 2010), mid-infrared spectral libraries (Dangal et al 2019), and Diffuse Reflectance Fourier-Transformed Infrared (DRIFTS, Kaiser and Ellerbrock 2005;Leue et al 2010). Substrate chemistry is represented in fine-scale biogeochemical models (e.g.…”
Section: Research Opportunities For Integrating Microbial and Biogeochemical Modelling Approachesmentioning
confidence: 99%
“…This topic has received considerable attention from multiple scientific domains over the past few decades, resulting in parallel advances between biogeochemical and microbial research (Fig. 1) and calls for greater diversity of measurements used within biogeochemical models (Billings et al 2021). Collectively, we have made outstanding progress in our understanding of global C cycles; however, a key opportunity remains in integrating theoretical and modelling frameworks from different scientific domains.…”
Section: Introductionmentioning
confidence: 99%